Genome-Wide Analysis of DNA Methylation and Acute Coronary Syndrome. Issue 11 (26th May 2017) - Li, Jun; Zhu, Xiaoyan; Yu, Kuai; Jiang, Haijing; Zhang, Yizhi; Deng, Siyun; Cheng, Longxian; Liu, Xuezhen; Zhong, Jia; Zhang, Xiaomin; He, Meian; Chen, Weihong; et al.
Abstract : Rationale: : Acute coronary syndrome (ACS) is a leading cause of death worldwide. Immune functions play a vital role in ACS development; however, whether epigenetic modulation contributes to the regulation of blood immune cells in this disease has not been investigated. Objective: : We conducted an epigenome-wide analysis with circulating immune cells to identify differentially methylated genes in ACS. Methods and Results: : We examined genome-wide methylation of whole blood in 102 ACS patients and 101 controls using HumanMethylation450 array, and externally replicated significant discoveries in 100 patients and 102 controls. For the replicated loci, we further analyzed their association with ACS in 6 purified leukocyte subsets, their correlation with the expressions of annotated genes, and their association with cardiovascular traits/risk factors. We found novel and reproducible association of ACS with blood methylation at 47 cytosine-phosphoguanine sites (discovery: false discovery rate <0.005; replication: Bonferroni corrected P <0.05). The association of methylation levels at these cytosine-phosphoguanine sites with ACS was further validated in at least 1 of the 6 leukocyte subsets, with predominant contributions from CD8 + T cells, CD4 + T cells, and B cells. Blood methylation of 26 replicated cytosine-phosphoguanine sites showed significant correlation with expressions of annotated genes (including IL6R, FASLG, and CCL18 ; P <5.9×10 −4 ), and differential gene expression in case versus controls corroborated the observed differential methylation. The replicated loci suggested a role in ACS-relevant functions including chemotaxis, coronary thrombosis, and T-cell–mediated cytotoxicity. Functional analysis using the top ACS-associated methylation loci in purified T and B cells revealed vital pathways related to atherogenic signaling and adaptive immune response. Furthermore, we observed a significant enrichment of the replicated cytosine-phosphoguanine sites associated with smoking and low-density lipoprotein cholesterol ( P enrichment ⩽1×10 −5 ). Conclusions: : Our study identified novel blood methylation alterations associated with ACS and provided potential clinical biomarkers and therapeutic targets. Our results may suggest that immune signaling and cellular functions might be regulated at an epigenetic level in ACS. Abstract : Supplemental Digital Content is available in the text.